2020
DOI: 10.21203/rs.3.rs-87868/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cross-linking peptide and repurposed drugs inhibit both entry pathways of SARS-CoV-2

Abstract: So far, effective antivirals have not been widely available for treating COVID-19. In this study, we identify a dual-functional cross-linking peptide 8P9R which can inhibit the two entry pathways (endocytic pathway and TMPRSS2-mediated surface pathway) of SARS-CoV-2 in cells. The endosomal acidification inhibitors (8P9R and chloroquine) can synergistically enhance the activity of arbidol, a spike-ACE2 fusion inhibitor, against SARS-CoV-2 and SARS-CoV in cells. In vivo studies indicate that 8P9R or the combinat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Although targeting acidification might have several side effects in a physiological setting, A(H1N1)pdm09 infected mice showed better outcomes upon intranasal treatment with P9R [ 116 ]. A follow up study, currently available as preprint, suggests that virus-binding P9R-derived oligomers may cross-link viral particles [ 117 ]. The analyzed eight-branched 8P9R is more potent than P9R in blocking SARS-CoV-2 entry and also inhibits infection of TMPRSS2 positive Calu-3 cells by aggregating viral particles, confirming its dual-antiviral mechanism.…”
Section: Targeting Proteolytic S Protein Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although targeting acidification might have several side effects in a physiological setting, A(H1N1)pdm09 infected mice showed better outcomes upon intranasal treatment with P9R [ 116 ]. A follow up study, currently available as preprint, suggests that virus-binding P9R-derived oligomers may cross-link viral particles [ 117 ]. The analyzed eight-branched 8P9R is more potent than P9R in blocking SARS-CoV-2 entry and also inhibits infection of TMPRSS2 positive Calu-3 cells by aggregating viral particles, confirming its dual-antiviral mechanism.…”
Section: Targeting Proteolytic S Protein Activationmentioning
confidence: 99%
“…The antiviral effect was confirmed in vivo in mice and hamsters where its application decreased viral loads. In contrast, the TMPRSS2 inhibitor camostat mesylate was inactive, further illustrating that blocking only one entry pathway might be insufficient [ 117 ].…”
Section: Targeting Proteolytic S Protein Activationmentioning
confidence: 99%
“…SARS-CoV-2 mainly depended on two pathways (TMPRSS2 mediated membrane fusion pathway and cathepsin B/L mediated endocytic pathway) to enter cells (36). Previous studies showed that SARS-CoV-2 entry into the Vero E6 cells mainly through the endocytic pathway due to the low expression of TMPRSS2 in this cell.…”
Section: Discussionmentioning
confidence: 97%
“…No drugresistant virus was found after 20 viral passages in the presence of P16. Interestingly and importantly, chloroquine, despite not showing effective antiviral activity in vivo (23,24,29,30) when administrated through systemic routes in many studies, could target host endosomes to block pH-dependent viral infection and signi cantly inhibit in uenza virus and coronavirus replication in mice and hamsters when administrated by intranasal routes. The host-targeting antiviral activity of chloroquine indicates that chloroquine is less likely to induce drug-resistant problem.…”
Section: Discussionmentioning
confidence: 99%
“…These in vivo data provided the information that the endosomal acidi cation inhibitor chloroquine, which could not inhibit coronavirus or in uenza virus replication in vivo when administrated by oral inoculation ( Supplementary Fig. 14) or intraperitoneal injection (24,25,29,30), might effectively inhibit coronavirus and in uenza virus replication in humans if chloroquine could be administrated to lungs by intranasal routes to provide effective chance of keeping lung cells in the bath of chloroquine environment. Thinking about the TMPRSS2-mediated entry pathway of SARS-CoV-2 in humans, we further demonstrated that chloroquine could signi cantly inhibit SARS-CoV-2 replication in ex vivo human lung tissues which were kept in the bath of chloroquine (Fig.…”
Section: Endosomal Acidi Cation Inhibitors Against Viruses In Vivomentioning
confidence: 97%